Competences of Preschool Parents and Teachers in the Early Detection of Preschool Children at Risk of Dyslexia - Ibrahim, Rohaizat; Shanmugavel, Rathana; Omar, Rosmaria (International Journal of Pedagogy and Learning Community (IJPLC), 2024)
Children at risk for dyslexia experience disorders that affect their reading ability. These disorders occur throughout life, resulting in their lives not being aligned with normal children. Thus, this study aims to identify the competencies of parents and preschool teachers in terms of knowledge, skills, and attitudes towards the early detection of preschool children at risk of dyslexia. A quantitative design using a questionnaire instrument was used in this study. A total of one hundred and eleven preschool teachers and eighty parents with children in preschool were involved in this study. The overall findings indicated that knowledge there was no significant relationship between the competencies of parents and preschool teachers in terms of knowledge, skills, and attitudes towards the early detection of preschool children at risk of dyslexia. This study shows that parents and preschool teachers have a moderate level of competence. The study's findings also show that the majority of preschool children have no early detection of Dyslexia. The fact is that the early detection can bring well-being to these children's lives in the future.